An analysis of radioactivity distribution in soil particles using an autoradiogram method. Issue 1 (1st January 2017) - Ohnuma, Tohru; Ishii, Keizo
Abstract: More than 22, 000, 000 m 3 of soil was contaminated with cesium (Cs) radioisotopes following the accident at the Fukushima Daiichi Nuclear Power Plant. For site remediation, it is necessary to reduce this huge volume of contaminated soil. To achieve this, we investigated the distribution of contamination within soil particles. We measured the radioactivity distribution in soil particles using an autoradiogram (ARG) method, with a resolution of 50 × 50 μm, and also determined the elemental distributions with energy-dispersive X-ray spectroscopy. The ARG showed that almost all particles were uniformly contaminated with Cs radioisotopes, while the elemental distributions indicated that the particles were clay aggregates. These results suggest that, by impacting contaminated particles with each other and classifying them, we can reduce the volume of contaminated soil.